Mitigation of Diabetes Mellitus Using Euphorbia helioscopia Leaf Ethanolic Extract by Modulating GCK, GLUT4, IGF, and G6P Expressions in Streptozotocin-Induced Diabetic Rats - Ahmed Raza; Muhammad Naveed Mushtaq; Sadia Hassan; Ali Sharif; Bushra Akhtar; Muhammad Furqan Akhtar (Journal of Diabetes Research)
Diabetes mellitus is a metabolic disorder. Synthetic antidiabetics are the commonly used treatment options associated with complications. The objective of this study was to explore the antioxidative and antidiabetic potential of Euphorbia helioscopia whole plant ethanolic extract using in vitro and in vivo models. For that purpose, the antioxidative potential was explored by using 2,2-diphenyl-1-picrylhydrazyl analysis. In vitro antidiabetic potential of the extract was evaluated using amylase inhibitory analysis. In vivo antidiabetic activity of the extract was assessed in diabetic rats using streptozotocin/nicotinamide (60 mg/kg/120 mg/kg) as an inducing agent. Metformin was used as standard. The results indicated the presence of significant quantities of phenolic 82.18±1.28 mgg−1 gallic acid equivalent (GAE) and flavonoid 66.55±1.22 mgg−1 quercetin equivalent (QE) contents in the extract. Quantitation of phytoconstituents exhibited the presence of sinapic acid, myricetin, and quercetin using HPLC analysis. The extract inhibited α-amylase by 84.71%, and an antiglycemic potential of 50.34% was assessed in the OGTT assay. Biochemical analysis demonstrated a reduction in urea, creatinine, cholesterol, low-density lipoprotein, and alkaline phosphatase (p<0.001) as compared to diabetic control rats at the dose of 500 mg/kg. An upregulation in the expressions of glucokinase, glucose transporter 4, peroxisome proliferator-activated receptor γ, and insulin-like growth factor was observed in treated rats in contrast to G6P expression, which was downregulated upon treatment. In conclusion, this study provided evidence of the antioxidative and antidiabetic potential of E. helioscopia whole plant ethanolic extract through in vitro and in vivo analysis and emphasized its promising role as a natural alternative.